The Temporary Parentheses: César Vallejo’s Letters in Exile - Echevarría, Andrés (2019)
In September 1927, César Vallejo tells Pablo Abril de Vivero on a letter: «Until now I live under a temporary parentheses, always on the doors of another kind of existence, one which, I repeat, it never comes. I take everything like this: with a provisional character». Beyond a biographical speculation, the letters reveal, from the poet’s voice, the labyrinths where he had to walk in Europe: financial trouble, illness, passion, projects, political thinking, description of geographical and historical contexts, success, and adversity. By researching and comparing Vallejo’s attitudes towards different individuals, and by analyzing the emotional situations and opinions that these documents evince, I will approach to the poet’s perspective and to his lyric voice, which —immerse in some of the most trascendental scenes of the twentieth century— reflects on the unfathomable human condition.